Antiviral Therapy Reduces Viral Burden but Does Not Prevent Thymic Involution in Young Cats Infected with Feline Immunodeficiency Virus - Hayes, Kathleen A. (American Society for Microbiology, 2000)
The thymus is a major target organ in human immunodeficiency virus type 1 (HIV-1)-infected children and feline immunodeficiency virus (FIV)-infected young cats (G. A. Dean and N. C. Pedersen, J. Virol. 72:9436–9440, 1998; J. L. Heeney, Immunol. Today 16:515–520, 1995; S. M. Schnittman et al., Proc. Natl. Acad. Sci. USA 87:7727–7731, 1990; T. A. Seemayer et al., Hum. Pathol. 15:469–474, 1984; H.-J. Shuurn et al., Am. J. Pathol. 134:1329–1338, 1989; J. C. Woo et al., J. Virol. 71:8632–8641, 1997; J. C. Woo et al., AIDS Res. Hum. Retrovir. 15:1377–1388, 1999). It is likely that the accelerated disease process in children and cats is due to infection of the thymus during the time when generation of naive T lymphocytes is needed for development of the mature immune system. Zidovudine (ZDV) monotherapy, which is used to prevent and treat perinatal HIV-1 infection (R. Sperling, Infect. Dis. Obstet. Gynecol. 6:197–203, 1998), previously had been shown to reduce viral burden in FIV-infected young cats (K. A. Hayes et al., J. Acquir. Immune Defic. Syndr. 6:127–134, 1993). The purpose of this study was to evaluate the effect of drug-induced reduction of viral burden in the thymus on virus-mediated thymic involution and peripheral blood CD4 decline using FIV-infected cats as a model for pediatric HIV-1 infection. Eight-week-old cats were randomly assigned to uninfected, saline-treated; uninfected, ZDV-treated; FIV-infected, saline-treated; and FIV-infected, ZDV-treated groups. Parameters measured included blood lymphocyte numbers, viral load in blood and thymic tissue, and thymic histopathology. While the viral burden was significantly reduced by ZDV monotherapy in peripheral blood lymphocytes, plasma, and thymus, thymic lesions were similar for the treated and untreated FIV-infected cats. Further, markedly lowering the viral burden did not increase blood CD4 lymphocyte numbers or prevent their decline. The data suggest that an inflammatory process continued in spite of reduced virus replication. These observations imply that reducing virus load and limiting thymic inflammation are separate factors that must be addressed when considering therapeutic strategies aimed at preserving thymic function.